'We are fireworks': Anarcho-punk, positive punk and democratic individuality. (1st June 2021) - White, Stuart
This article explores the tensions within and around anarcho-punk concerning individuality and individualism by drawing on George Kateb's discussion of the normative ideal of 'democratic individuality', developed to understand the work of the American Emersonian writers (Emerson, Thoreau, Whitman). The article elaborates the three core ideas of 'democratic individuality': positive, negative and impersonal individuality. The article interprets the work of Crass, a founding and influential band in the anarcho-punk scene, as centrally a passionate expression of negative individuality: the individual's refusal to be complicit with injustice. Engaging Rich Cross's work on individualism in anarcho-punk, the article explains how democratic individuality both supports and cautions against collective action, using this tension to explain the anxiety around collective action in Crass's work. Using Kateb's framework, the article argues that positive punk gives a different ‐ in the context, arguably corrective ‐ emphasis to individual self-expression (positive individuality) and self-transcendence (impersonal individuality). Democratic individuality connects punk/post-punk to a history of argument over what it means to become an 'individual'; and, going forward, offers a helpful framework for punk/post-punk communities in approaching this value.